Korelasi Trombosit dan Hematokrit Sebagai Indikator Klinis Awal pada Pasien Demam Berdarah Dengue di Rumah Sakit Metro Cikarang Utara - Tiffany Valerie Alexandra; Freddy Ciptono (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Dengue Hemorrhagic Fever (DHF) is an infectious disease caused by a virus, characterized by decreased platelet levels and increased hematocrit levels due to plasma leakage. The assessment of these two parameters is crucial in evaluating the clinical status and severity of the disease. This study aims to analyze the relationship between platelet count and hematocrit levels in patients with Dengue Hemorrhagic Fever (DHF) treated at Metro Cikarang Utara Hospital. An analytical quantitative approach with a cross-sectional design was used, involving data from 124 DHF patients. The analysis revealed that all patients experienced thrombocytopenia, with an average platelet count of 91,430/μL, while hematocrit levels varied, with an average of 42.56%. Spearman correlation test was employed, showing a significant negative correlation between platelet count and hematocrit levels (r = -0.268; p = 0.003). These findings indicate that the lower the platelet count, the higher the potential for increased hematocrit levels. This supports the correlation between thrombocytopenia and hemoconcentration due to plasma leakage, which is a hallmark of the critical phase of DHF. The results emphasize the importance of regular monitoring of these parameters for early detection of clinical deterioration and determination of appropriate clinical interventions.